Locators of the settlements under Wallachian law in the Sambor starosty in XVth and XVIth c. Territorial, ethnic and social origins. - Gawron, Jan (Balcanica Posnaniensia. Acta et studia, 2020)
This article deals with issues related to the origin of locators of the Wallachian settlements on the example of villages established in the Sambor starosty in the XVth and XVIth centuries. It relies primarily on the analysis of information found in the location documents of settlements arising in this area. The research carried out here leads to the conclusion that the first owners of the Wallachian villages in the Sambor starosty were the representatives of the Wallachian nobility, most probably from the Transylvania area, who received extensive land bestowals from the king Vladyslav Jagiello in the XVth century. From the knyazships founded by the nobility came the knyazes who founded new Wallachian villages within the royal domain in the XVIth century. They were mainly from the peasant estate, and most of them were recruited from the ruthenised knyaz families and from the subjects of the same domains. Although the ethnic Vlachs constituted a small percentage of residents of the Sambor starosty and were quickly subjected to ruthenisation, their descendants continued to lead the ranks among the locators. The work also draws attention to the characteristics of the development of the settlement network in the Sambor area. New settlements were most often created at a short distance from the home rural centres surrounding them from various directions. After some time, these "villages" could also become "home" for subsequent settlements. New settlements were usually located in areas situated higher than the home settlements of founders who, looking for new settlement areas, headed upstream as the rivers were natural communication routes.